Development of an Integrated Information System for Monitoring and Validation of Health Workers Practice Licenses (STR) in Healthcare Facilities - Kriswibowo, Rony; Agung Budi Setyawan; Rusina Widha Febriana (CV.RIZANIA MEDIA PRATAMA, 2025)
The management of Health Workers ' Registration Certificates (STR) in Indonesia faces challenges such as manual processing, data fragmentation, and the risk of expired or fake STR, which can endanger patient safety and hinder supervision by health facilities and authorities. This study developed a web-based information system using the Waterfall approach, through the stages of needs analysis, design, implementation, testing (Black Box and User Acceptance Testing), and deployment on Anwar Medika University servers, with centralized database features, automatic notifications, QR code verification, and compliance reports. As a result, the system improved efficiency, accuracy, and transparency, with 87% of respondents rating the intuitive interface and service satisfactory, 89% felt the time efficiency, and 95% considered the system easy to use. The system is recommended to be widely implemented, integrated with the national e-Health, with regular maintenance and training of users to support the management of accountable and qualified health personnel.